Overexpression of Banna mini‐pig inbred line fatty acid binding protein 3 promotes adipogenesis in 3T3‐L1 preadipocytes. (28th April 2014) - Yi, Bao; Wang, Jigui; Wang, Shuang; Yuan, Daoli; Sun, Jiazeng; Li, Zhili; Mao, Yaping; Hou, Qiang; Liu, Weiquan
Abstract Fatty acid binding protein 3 (H‐FABP, FABP3) has been significantly associated with intramuscular fat (IMF) content in pigs, which is positively correlated with palatability of pork. However, its underlying function is not fully elucidated. We have investigated the effects of overexpression of the FABP3 gene on differentiation and adipogenesis of 3T3‐L1 preadipocytes in the fat Banna mini‐pig inbred line (fBMIL). Eukaryotic vectors that expressed the FABP3 protein were constructed, and stably established in the 3T3‐L1 preadipocytes cell line. Cells were induced in a standard differentiation cocktail. Morphological changes and the degree of adipogenesis were measured by Oil Red O staining assay and triacylglycerol content measurement, respectively. mRNA expression levels of triacylglycerol metabolism‐related genes were measured by qPCR. FABP3 significantly promoted differentiation of 3T3‐L1 cells and enhanced triacylglycerol levels (P < 0.05). mRNA of the peroxisome proliferator‐activated receptor γ (PPARγ), adipocyte fatty acid binding protein (422/aP2) and glycerol‐3‐phosphate dehydrogenase (GPDH) gene increased markedly (P < 0.05). In conclusion, expression of the FABP3 gene enhances adipogenesis in 3T3‐L1 preadipocytes primarily by upregulating lipogenic PPARγ, 422/aP2 and GPDH genes.